2010
DOI: 10.1007/s12275-010-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of biogenic amine-producing bacteria in fermented soybean pastes

Abstract: Biogenic amines (BAs) are produced primarily by microorganisms found in fermented foods and are often implicated in food poisoning. BA-producing bacteria found in fermented soybean pastes were isolated and characterized using a decarboxylating medium and multiplex PCR analysis. Two BA-producing bacteria were isolated from traditional soybean pastes: one was a histamine-producing Clostridium strain, and the other was a tyramine-producing Pseudomonas strain. The Clostridium strain was determined to be a potent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…BAs including putrescine, cadaverine, spermidine, histamine, and tyramine are low‐molecular‐weight nitrogenous organic compounds that are produced by microbial decarboxylation of the corresponding amino acids and nitrogen compounds during food fermentation (Silla Santos ; Moon and others ; Costantini and others ; Qi and others ). It is well known that the excessive consumption of BAs can induce adverse effects such as nausea, respiratory distress, hot flushes, heart palpitations, headache, and hyper‐ or hypotension (Silla Santos ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAs including putrescine, cadaverine, spermidine, histamine, and tyramine are low‐molecular‐weight nitrogenous organic compounds that are produced by microbial decarboxylation of the corresponding amino acids and nitrogen compounds during food fermentation (Silla Santos ; Moon and others ; Costantini and others ; Qi and others ). It is well known that the excessive consumption of BAs can induce adverse effects such as nausea, respiratory distress, hot flushes, heart palpitations, headache, and hyper‐ or hypotension (Silla Santos ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to find strategies to prevent or reduce the production of BAs during ganjang fermentation. Although BAs are frequently found in Korean traditional fermented soybean foods such as doenjang (fermented soybean pastes) and ganjang, studies on the microorganisms responsible for BA production are limited to doenjang fermentation and mainly based on decarboxylase activity alone (Cho and others ; Lee and others ; Moon and others ; Shukla and others ; Chang and Chang ). To the best of our knowledge, this is the first study to reveal the microorganisms that are mainly responsible for BA production during ganjang fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…practices could originate a contamination with microorganisms owing histidine and tyrosine decarboxylase activity. Different species isolated from fermented soybean products of genera of Clostridium, Bacillus, Enterococci, Enterobacteria and Pseudomonas have been reported as TY and HI producers (Nout, Ruiker, & Bouwmeester, 1993;Han, Beumer, Rombouts, & Nout, 2001;Tsai, Chang, & Kung, 2007;Moon et al, 2010;. According to Guan et al (2013), to minimise the biogenic amine contents, sufu should be produced under strict hygienic conditions.…”
Section: Biogenic Amines In Soybean Productsmentioning
confidence: 99%
“…Amine-producing lactic bacteria such as Lactobacillus breuis, Lactobacillus buchneri, Lactobacillus bulgaricus, Lactobacillus curuatus, Lactobacillus carnis, Lactobacillus dicergens and Lactobacillus hilgardii have bee n isolated fro m meat products (Maijala et al, 1993). Moon et al (2010) isolated two biogenic amine producing bacteria from traditional soybean pastes: one was a histamine producing Clostridium strain, and the other was a tyramine producing Pseudomonas strain. Moon et al (2010) reported that Clostridium strain, isolated from traditional soybean pastes, was potent histamine producer among the tested cultures.…”
Section: Microorganisms Producing Biogenic Amine In Soybean Foodmentioning
confidence: 99%
“…Moon et al (2010) isolated two biogenic amine producing bacteria from traditional soybean pastes: one was a histamine producing Clostridium strain, and the other was a tyramine producing Pseudomonas strain. Moon et al (2010) reported that Clostridium strain, isolated from traditional soybean pastes, was potent histamine producer among the tested cultures. Clostridium perfringens grows in protein rich media and can not survive in media that lacks essential amino acid supply (Shimizu et al, 2002).…”
Section: Microorganisms Producing Biogenic Amine In Soybean Foodmentioning
confidence: 99%